RESPONSE OF TURMERIC SHOOT EXPLANT AFTER CYTOKININ WITH IN VITRO - Marhan Nurullia; Erni Suminar Suminar; Anne Nurani (Jurnal Penelitian Saintek, 2019)
This study was aimed at determining the response of turmeric shoot explants after the provision of various types and concentrations of cytokinins in vitro. This experiment was conducted at the Tissue Culture Laboratory, Faculty of Agriculture, Padjadjaran University from January to April 2018. The data were analyzed using T-Test. The experimental method used in this research was Completely Randomized Design (CRD). Explant planting was carried out in Laminar Air Flow. The experiment consisted of 7 treatments consisting of 4 replications and each test consisted of 4 units. Observation of this experiment was carried out for 12 MST. The main observations were made on the data that were tested statistically namely the percentage of explant growing shoots, percentage of explant growing roots, shoot height, number of tuns, number of roots and root length. The treatments consisted of Control, 2.5 mg L-1 BAP, 5 mg L-1 BAP, 0.5 mg L-1 TDZ, 1 mg L-1 TDZ, 0.01 mg L-1 Zeatin and 0.1 mg L Zeatin -1. The results show that the treatment of 1 mg L-1 TDZ shows the best response to the growth of turmeric explants by increasing the number of turmeric shoot explants than the others.RESPONS EKSPLAN TUNAS KUNYIT SETELAH SITOKININ SECARA IN VITROTujuan dari penelitian ini yaitu untuk melihat respons eksplan tunas kunyit terhadap pemberian berbagai jenis dan konsentrasi sitokinin secara in vitro. Percobaan ini dilakukan di Laboratorium Kultur Jaringan, Fakultas Pertanian, Universitas Padjadjaran dari bulan Januari sampai April 2018. Hasil percobaan dianalisis dengan Sample T-Test. Metode percobaan yang digunakan dalam penelitian ini yaitu Rancangan Acak Lengkap (RAL). Penanaman eksplan dilakukan di dalam Laminar Air Flow. Percobaan terdiri dari 7 perlakuan sebanyak 4 ulangan dan setiap ulangan terdiri dari 4 unit. Pengamatan percobaan ini dilakukan selama 12 MST. Pengamatan utama dilakukan terhadap data-data yang diuji secara statistik yakni persentase eksplan tumbuh tunas, persentse eksplan tumbuh akar, tinggi tunas, jumlah tunas, jumlah akar dan panjang akar. Perlakuan terdiri dari Kontrol; 2,5 mg L-1 BAP; 5 mg L-1 BAP; 0,5 mg L-1 TDZ; 1 mg L-1 TDZ; 0,01 mg L-1 Zeatin; dan 0,1 mg L-1 Zeatin. Hasil penelitian menunjukkan bahwa perlakuan 1 mg L-1 TDZ menunjukkan respons yang lebih baik terhadap pertumbuhan eksplan kunyit dengan meningkatkan jumlah tunas eksplan tanaman kunyit daripada yang lainnya.